FRI0178 Rituximab is effective in the treatment of rheumatoid arthritis regardless of body mass index. (15th June 2017) - Yoo, DH; Park, W; Suh, CH; Shim, SC; Lee, SJ; Bae, YJ; Park, C; Koo, JH
Abstract : Background: High body mass index (BMI) is known to be associated with inadequate clinical response to anti-TNF agents in rheumatoid arthritis (RA) patients. 1 However, there are limited data on the effect of high BMI on the response to rituximab in RA patients, who showed an inadequate response or intolerance to anti-TNF agents. Objectives: To investigate the impact of BMI on clinical response in the post-hoc analysis of randomized controlled trial that demonstrated clinical equivalence between a biosimilar of rituximab, CT-P10 and innovator rituximab, RTX 2 (NCT02149121 ). Methods: A total of 332 patients who received two courses of either CT-P10 or RTX were included in this analysis. Patients were classified into 3 groups; normal weight (<25kg/m 2 ), overweight (≥25 kg/m 2 ) and obesity (≥30 kg/m 2 ) as per WHO BMI category. Improvement in disease activity by the Disease Activity Score using C-reactive protein (DAS28-CRP), remission (≤2.6), low disease activity rate (LDA, ≤3.2) and ACR response at Week 24 (Week 24 of 1st course) and Week 48 (Week 24 of 2nd course) and duration of sustained LDA (from the first LDA observed to the last LDA observed up to Week 48) were analysed by BMI categories in the each and combined group of CT-P10 and RTX. Results: In the pooled group of CT-P10 and RTX, the mean weights were 59 kg in normal weight, 73kg in overweight and 91kg in obesity. All other baseline characteristics were comparable among BMI groups including baseline disease activity based on DAS28; Moderate disease activity, 22.3% vs. 22.8% vs. 25.7%, respectively; High disease activity, 77.7% vs. 77.2% vs. 74.3%, respectively. There was no statistical difference among BMI groups in terms of DAS28 change from baseline and ACR 20/50/70 response (Table). No particular trend was observed in remission and LDA rate by DAS28 at Week 24 and Week 48 among BMI groups (Figure). Mean duration of sustained LDA (months) were also comparable among the groups (4.5 vs. 4.7 vs. 5.0, respectively). Additionally, similar trends in all analyses were observed in each treatment group; CT-P10 and RTX. Conclusions: The BMI does not affect the clinical response in RA patients with rituximab treatment. Therefore, this result supports that rituximab could be a reasonable therapeutic option for obese RA patients with inadequate response to anti-TNF agents. References: Gremese E et al. Arthritis Care Res (Hoboken) 2013;65:94–100. Yoo DH, et al. American College of Rheumatology 2016; Abstract No. 1635. Disclosure of Interest: D. H. Yoo Consultant for: Celltrion Inc., W. Park Consultant for: Celltrion Inc., C. H. Suh Consultant for: Celltrion Inc., S. C. Shim Consultant for: Celltrion Inc., S. J. Lee Employee of: Celltrion Inc., Y. J. Bae Employee of: Celltrion Inc., C. Park Employee of: Celltrion Inc., J. H. Koo Employee of: Celltrion Inc.